Use of alcohol, tobacco and coffee, and risk of pancreatic cancer. - Heuch, I. (Nature Publishing Group, 1983)
Associations between pancreatic cancer and use of alcohol, tobacco and coffee were examined in a Norwegian prospective study of 16,713 individuals in which 63 cases occurred. The associations were assessed using techniques for stratified logistic regression. Of the potential risk factors considered, use of alcohol showed the strongest positive association, with an estimated relative risk of 5.4 for those with a frequent use as compared with non-drinkers (P less than 0.001). A clear positive association was also obtained with chewing of tobacco or use of snuff. For cigarette smoking a somewhat weaker association was observed. No association could be established for pipe smoking or coffee drinking. In general, more clear-cut results were found when analysis was restricted to histologically-verified cases.